Weaving and Detail Filling of Willow Weaving Frame Based on AI Intelligent Design - Zuo, Lingqun (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: Willow weaving is a traditional Chinese handicraft with profound historical and cultural value. However, in the context of modernization, it faces significant challenges including a generational gap in skill inheritance, low production efficiency, limited design innovation, and difficulties in quality control. Contribution: This study contributes to the revitalization of intangible cultural heritage while enhancing the market relevance of the craft. Method: The research applied a descriptive qualitative approach using both primary and secondary data. Methods included historical data analysis, AI-assisted design modelling, development of digital learning platforms and VR simulation systems, and the implementation of image recognition technology for quality control. Results: The integration of AI enabled the generation of innovative design solutions based on trend analysis and consumer preferences. Automation improved production efficiency, and AI image recognition ensured consistent product quality through real-time defect detection. Additionally, the virtual learning system effectively supported the transfer of weaving skills to younger generations. Conclusion: AI technology plays a vital role in modernizing traditional willow weaving. Its application not only enhances product uniqueness and efficiency but also offers a sustainable strategy for preserving intangible cultural heritage in the digital era.